Axial heterogeneity of bicarbonate, chloride, and water transport in the rat proximal convoluted tubule. Effects of change in luminal flow rate and of alkalemia. - Liu, F Y (1986)
These studies examined regulation of superficial proximal convoluted tubule (PCT) transport as a function of length. When single nephron glomerular filtration rate (SNGFR) increased from 28.7 +/- 0.7 nl/min in hydropenia to 41.5 +/- 0.4 nl/min in euvolemia, bicarbonate, chloride, and water reabsorption in the early (1st mm) PCT increased proportionally: from 354 +/- 21 peq/mm X min, 206 +/- 55 peq/mm X min, and 5.9 +/- 0.4 nl/mm X min to 520 +/- 12 peq/mm X min, 585 +/- 21 peq/mm X min, and 10.1 +/- 0.4 nl/mm X min, respectively. These high transport rates did not increase further, however, when SNGFR went to 51.2 +/- 0.7 or 50.7 +/- 0.6 nl/min after atrial natriuretic factor or glucagon administration. Anion and water transport rates in the late PCT were lower and exhibited less flow dependence. During chronic metabolic alkalosis, acidification was inhibited in the late but not early PCT. In conclusion, the early PCT is distinguished from the late PCT by having high-capacity, flow-responsive but saturable, anion- and water-reabsorptive processes relatively unaffected by alkalemia.